Impact of ground-glass component on prognosis in early-stage lung cancer treated with stereotactic body radiotherapy via Helical Tomotherapy - Jintao Ma; Shaonan Fan; Wenhan Huang; Xiaohong Xu; Yong Hu; Jian He (Radiation Oncology)
Abstract Purpose This study aims to investigate the prognostic impact of ground-glass opacity (GGO)-component in early-stage lung cancer patients treated with stereotactic body radiotherapy (SBRT). Methods From January 2013 to December 2022, 239 early-stage lung cancer patients (T1-2N0M0) underwent SBRT. They were categorized into two groups based on the presence of GGO-component: 65 patients in the subsolid group with a consolidation tumor ratio (CTR) between 0.25 and 1 and 174 patients in the solid group with a CTR of 1. Lung cancer-specific survival (LCSS) and progression-free survival (PFS) were analyzed using Cox regression models for both univariate and multivariate analyses to identify prognostic factors. Stabilized inverse probability of treatment weighting (IPTW) was employed for adjusting confounding factors. Recurrence incidence was assessed using competing risk analysis and compared using Gray’s test. Results In the multivariate analysis, female, peripheral location, and subsolid nodules were favorable prognostic factors for LCSS; peripheral location, subsolid nodules, and adjuvant therapy were favorable prognostic factors for PFS. Between the subsolid (n = 65) and solid groups (n = 174), the median LCSS were not reached (p = 0.003), with 3-, 5-, and 9-year LCSS rates of 94.7% versus 80.3%, 90.9% versus 64.1%, 82.7% versus 53.5%, respectively. The median PFS were 72.5 months and 50.5 months (p = 0.030), with 3-, 5-, and 9-year PFS rates of 75.4% versus 61.2%, 56.6% versus 44.9%, 48.6% versus 23.3%, respectively. After stabilized IPTW (n = 240), the median LCSS were not reached (p = 0.024), with 3-, 5-, and 9-year LCSS rates of 94.0% versus 82.4%, 92.2% versus 67.7%, 85.3% versus 58.2%, respectively. The median PFS were 60.2 months and 50.5 months (p = 0.096), with 3-, 5-, and 9-year PFS rates of 73.8% versus 61.0%, 53.5% versus 46.2%, 46.8% versus 22.4%, respectively. The subsolid group had lower rates of locoregional recurrence (LRR) (10.4% vs. 25.9%, p = 0.035) and distant metastasis (DM) (17.1% vs. 37.9%, p = 0.064) compared to the solid group. Conclusions The presence of GGO-component in the lesion is an independent prognostic factor for LCSS and PFS. Subsolid nodules treated with SBRT demonstrated better prognosis, with significantly lower rates of local-regional recurrence. We should highlight GGO-component as a practical indicator for risk stratification of SBRT patients to guide treatment decisions.